Linkages between literary response, aesthetic competence, and literary competence in the EFL classroom. (December 2022) - Calafato, Raees; Simmonds, Kevin
Abstract: Developing students' literacy skills and intercultural competence via literary works has become a key component of foreign language (FL) curricula at the primary, secondary, and tertiary levels in many countries. In FL classrooms, the use of textual literature can also sometimes be complemented by multimodal literature like graphic novels and picture books, which are useful in enhancing the ability of students to interpret, synthesize, and analyze information from multiple media simultaneously. This article reports the findings from an online questionnaire-based study involving 265 university students in France who were studying English as an FL alongside their degree programs. The study explored their reported literary reading response, literary competence when reading textual and multimodal literature, aesthetic competence, and the extent to which their aesthetic competence and literary response predicted their literary competence. The findings indicated that participants' literary response drew strongly from Story-Driven Reading while their literary competence was significantly lower for textual literature than for multimodal literature. Moreover, their literary competence was statistically significantly predicted by certain components of their literary response and, to some extent, their aesthetic competence. Highlights: Participants' literary response drew most strongly on Story-Driven Reading. Multimodal literary competence was positively predicted by aesthetic competence. Literary preferences correlated weakly with participants' literary competence.